2020
DOI: 10.21037/jgo-20-122
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative computed tomography-assessed skeletal muscle index is a novel prognostic factor in patients with hepatocellular carcinoma following hepatectomy: a meta-analysis

Abstract: Background: Recently, several studies have examined the association between preoperative sarcopenia and prognosis evaluation in patients with hepatocellular carcinoma (HCC) undergoing hepatectomy. However, their conclusions remain ambiguous and controversial. Thus, we conducted a meta-analysis to assess the prognostic role of preoperative sarcopenia in patients with HCC undergoing hepatectomy. Methods: We searched the existing literature reporting on the prognostic value of preoperative computed tomography (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Previous meta-analyses for several other primary malignancies, including hepatocellular carcinoma and colorectal cancer, have found a decreased OS and RFS in sarcopenic patients. 9,[29][30][31] The effect size found in these cancers was somewhat higher (OS 1.57-1.83; RFS 1.54-1.55). 29,31 Similar to the results of this meta-analysis, reported HRs for OS were generally higher than for DFS/RFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta-analyses for several other primary malignancies, including hepatocellular carcinoma and colorectal cancer, have found a decreased OS and RFS in sarcopenic patients. 9,[29][30][31] The effect size found in these cancers was somewhat higher (OS 1.57-1.83; RFS 1.54-1.55). 29,31 Similar to the results of this meta-analysis, reported HRs for OS were generally higher than for DFS/RFS.…”
Section: Discussionmentioning
confidence: 99%
“…9,[29][30][31] The effect size found in these cancers was somewhat higher (OS 1.57-1.83; RFS 1.54-1.55). 29,31 Similar to the results of this meta-analysis, reported HRs for OS were generally higher than for DFS/RFS. This suggests that sarcopenia mostly reflects an impaired performance status rather than unfavorable tumour biology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some prior studies also identified either low SMI or sarcopenia as indicative of recurrence and reduced survival for HCC patients undergoing hepatectomy [ 20 , 25 27 ]. However, this study indicated that preoperative SMI did not stratify liver-related mortality risk, which could be a result of different endpoint and additional adjuvant TACE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While some of the algorithms are complicated, CRP and serum albumin measurements are used more often as components of combined indices. 39 The use of sarcopenia to predict outcomes in patients with cancer has attracted more attention, including those with HCC [46][47][48] or colorectal liver metastases (CRLM) 49,50 undergoing hepatic resection. Previous studies also demonstrated that sarcopenia increased the risk of postoperative morbidity and longer hospital stay, as well as readmission rates, after partial liver resection for CRLM.…”
Section: Evaluation By Biochemical and Physical Factorsmentioning
confidence: 99%